2014
DOI: 10.7314/apjcp.2014.15.1.239
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NDRG2 Can Inhibit Neuroblastoma Cell Proliferation through Negative Regulation by CYR61

Abstract: Several recent studies have showed that the n-myc downstream regulated gene 2 (NDRG2) is a new tumor suppressor gene, and that it plays an important role in tumor suppression in several cancers or cancer cell lines. However, few studies focused on its function in neuroblastoma cells. In the present investigation, we demonstrated that NDRG2 overexpression inhibited their proliferation. Using a cDNA microarray, we found that overexpression of NDRG2 inhibited the expression of cysteine-rich protein 61 (CYR61), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…To determine the functional role of NDRG2 in neuroblastoma, overexpression of NDRG2 was induced in the neuroblastoma cell lines SK-N-SH and SH-SY5Y, which resulted in an increased expression of the tumor suppressor gene protocadherin 17 and differentiation-related genes such as Rsu1 and Smurf1, and the decreased expression of proliferation-related genes such as CYR61. NDRG2 overexpression could thereby reduce cell proliferation compared with control cells [73].…”
Section: Neuroblastomamentioning
confidence: 97%
“…To determine the functional role of NDRG2 in neuroblastoma, overexpression of NDRG2 was induced in the neuroblastoma cell lines SK-N-SH and SH-SY5Y, which resulted in an increased expression of the tumor suppressor gene protocadherin 17 and differentiation-related genes such as Rsu1 and Smurf1, and the decreased expression of proliferation-related genes such as CYR61. NDRG2 overexpression could thereby reduce cell proliferation compared with control cells [73].…”
Section: Neuroblastomamentioning
confidence: 97%
“…The associations between NDRG2 and cancer have been reported in neurologic tumors [ 19 , 51 57 ], gastrointestinal tumors [ 9 11 , 13 , 14 , 55 , 58 75 ], genitourinary tumors [ 12 , 76 82 ], breast cancer [ 21 , 83 85 ], lung cancer [ 15 , 86 ], thyroid cancer [ 83 , 87 ], fibrosarcoma [ 88 ], oral squamous-cell carcinoma [ 89 ], myeloid leukemia [ 90 ] and cervical cancer (Hela cells) [ 25 ] (Table 1 ). Collectively, NDRG2 expression is associated with the clinical features of tumors.…”
Section: Associations Between Ndrg2 and Cancermentioning
confidence: 99%
“…Accumulating studies have shown that NDRG2 is associated with various nervous system diseases, including tumors, ischemic stroke, hemorrhage, trauma, and neurodegenerative disorders [1,59]. NDRG2 was repeatedly reported to be downregulated in a variety of cerebral tumors, including glioma and meningioma [21,[60][61][62][63][64][65][66]. The transcription levels of human NDRG2 are significantly reduced in human glioblastoma tissues and human glioblastoma cell lines, and exogenous overexpression of NDRG2 repressed glioblastoma cell proliferation in vitro [2].…”
Section: Ndrg2 In Brain Tumors and Other Nervous System Diseasesmentioning
confidence: 99%